Biological adhesive based on carboxymethyl chitin derivatives and chitin nanofibers. (February 2015) - Azuma, Kazuo; Nishihara, Masahiro; Shimizu, Haruki; Itoh, Yoshiki; Takashima, Osamu; Osaki, Tomohiro; Itoh, Norihiko; Imagawa, Tomohiro; Murahata, Yusuke; Tsuka, Takeshi; Izawa, Hironori; Ifuku, Shinsuke; et al.
Abstract: Novel biological adhesives made from chitin derivatives were prepared and evaluated for their adhesive properties and biocompatibility. Chitin derivatives with acrylic groups, such as 2-hydroxy-3-methacryloyloxypropylated carboxymethyl chitin (HMA-CM-chitin), were synthesized and cured by the addition of an aqueous hydrogen peroxide solution as a radical initiator. The adhesive strength of HMA-CM-chitin increased when it was blended with chitin nanofibers (CNFs) or surface-deacetylated chitin nanofibers (S-DACNFs). HMA-CM-chitin/CNFs or HMA-CM-chitin/S-DACNFs have almost equal adhesive strength compared to that of a commercial cyanoacrylate adhesive. Moreover, quick adhesion and induction of inflammatory cells migration were observed in HMA-CM-chitin/CNF and HMA-CM-chitin/S-DACNF. These findings indicate that the composites prepared in this study are promising materials as new biological adhesives.